Synthesis, In silico and In vitro Analysis of Hydrazones as Potential Antituberculosis Agents - Thorat, Bapu R.; Mali, Suraj N.; Rani, Deepa; Yamgar, Ramesh S. (Current Computer - Aided Drug Design, 2021)
Tuberculosis (TB) is a major cause of mortality and illness as reported by the W.H.O in 2019. The WHO report also mentioned the fact that about 10.0 million people fell ill with tuberculosis in the year 2018. Hydrazide–hydrazones having azomethine group (–NH–N=CH–) connected with carbonyl group is reported for the number of bioactivities like anti-inflammatory, anticonvulsant, anticancer, antiviral and antiprotozoal. Objective: The objective of our current study is to design and synthesise more potent hydrazide– hydrazones, containing anti-tubercular agents. Methods: In the current study, we synthesized 10 hydrazones (3a-3j) by stirring corresponding benzohydrazides (2) with substituted aldehydes (1a-j) in ethanol as a solvent and acetic acid as a catalyst at room temperature. All synthesized compounds were characterized by various spectroscopic techniques including elemental analysis, ultraviolet–visible spectroscopy, fluorescence, fourier- transform infrared spectroscopy and nuclear magnetic resonance spectroscopy. Compounds (3a-3j) were tested for in vitro anti-TB activity using Microplate Alamar Blue Assay (MABA). Results: All our synthesized compounds (3a-3j) were found to be potent against Mycobacteria tuberculosis (H37RV strain) with MIC (minimum inhibitory concentrations) values of 3.125-50 μg/mL. The hydrazide CO-NH protons in (3a-j) compounds are highly deshielded and showed broad singlet at 9.520-9.168 ppm. All the compounds were found to have more intense emission in the 416 – 429 nm regions and strong absorption in the regions of 316 – 327 nm. Synthesized compounds were also tested for in silico analysis using different software for their Absorption, Distribution, Metabolism, Excretion and Toxicity (ADMET) analysis. All the compounds were found to be in silico non-carcinogenic. Conclusion: It will be worth saying that our in silico and in vitro approaches used in the current study will become a guide for medicinal chemists to make structural modifications and synthesize more effective and potent hydrazone containing anti-tubercular agents.
Keywords: synthesis